Talent Management Strategy In Retaining Millennial Generation In The Workplace - Rio Mattajang (Journal Arbitrase : Economy, Management and Accounting, 2023)
The millennial generation, which is an increasingly dominant workforce, has different preferences, values and work styles than previous generations. This creates a challenge for organizations to retain and motivate millennial employees to remain productive and contribute optimally. This research aims to investigate effective talent management strategies in retaining the millennial generation in the workplace. This research uses a qualitative approach with descriptive methods. The research results highlight the need for a holistic approach in managing the millennial generation in the workplace. Findings show that the millennial generation tends to seek balance between work and personal life and prioritizes clear career development and work flexibility. Effective talent management strategies include providing structured career development, work flexibility, investment in training and development, and creating an inclusive and collaborative work culture. Research also emphasizes the importance of constructive feedback, open communication, and consistency in implementing company values as key factors in maintaining millennial generation engagement and retention.